Investigating the Effects of Am rap and Classic Cross-fit Training in Freestyle Wrestlers on Physical Fitness Parameters: Life Sciences-Sports and performance - Ali Türker; Oğuzhan Yüksel (International Journal of Life Science and Pharma Research, 2022)
This study aims to investigate anaerobic strength alterations of wrestlers who perform AMRAP (As many reps as possible) and Classic CrossFit pieces of training. The research was implemented on 32 male wrestlers who were challenged in the Turkish Wrestling 1st League in the season of 2018-2019. The volunteer participants taken part in test groups performed CrossFit models in the preseason for 8-weeks; Group I (Classic CrossFit) and Group II (CrossFit AMRAP). Bodyweight, height, and age values were recorded respectively by creating measuring parkour and arranged on MS Excel spreadsheet program. Two-factor variance analysis was used in repetitive measurements for identifying the differences between pre and final measuring anaerobic strength values of the participants. As findings, it was observed there was a significant difference in terms of group x time interaction dimension in back squat movement, 1 min on behalf of AMRAP. According to the simple effect test results, there were significant values in both groups. The numerical increase in some performance values of the AMRAP CrossFit training group after 8-weeks of training was more prominent than the classic CrossFit training group. In addition, AMRAP CrossFit training was effective in reducing body weight. Both models were found to have a positive effect on their physical capacities effectively. Although there are studies on CrossFit in the literature, there is no significant study on AMRAP and thus this study might be the pioneer in terms of contributions to the literature and lead to further comments on sports science as well. Thus, this study is significant to reveal the effectiveness of Amrap and CrossFit training on physical fitness parameters.